Surrogaatmoederskap: ’n teologies-etiese beoordeling - Bruyn, P. J. de (Koers, 1991)
Surrogate motherhood is the process by which a woman (the surrogate mother) conceives, carries and gives birth to a child for another woman or couple. Surrogate motherhood is related to issues such as masturbation, artificial insemination, in vitrofertilization (in vitro conception) and experimentation with embryos, which could entail the destruction or killing of embryos. Opinions about these matters would undoubtedly influence one’s perception of surrogate motherhood. Christians believe that conception in or outside the human body is made possible by God God gives life at the moment of conception. Therefore an embryo can never be considered as mere matter From a Christian point of view it is not imperative to condemn surrogate motherhood in all instances. Nevertheless, in view of what is taught in the Holy Scriptures and also because of certain practical implications, Christians cannot but be negative about the whole issue and would therefore hesitate to make use of such procedures.